Natural Disasters and Human Capital Accumulation - Cuaresma, Jesus Crespo (World Bank, 2012)
The empirical literature on the relationship between natural disaster risk and investment in education is inconclusive. Model averaging methods in a framework of cross-country and panel regressions show an extremely robust negative partial correlation between secondary school enrollment and natural disaster risk. This result is driven exclusively by geologic disasters. Exposure to natural disaster risk is a robust determinant of differences in secondary school enrollment between countries but not necessarily within countries.